The Cambridge companion to postmodernism - Connor, Steven, 1955- (Cambridge, UK ; New York : Cambridge University Press, 2004)
Offers a comprehensive introduction to postmodernism, examining the different aspects that have had a significant impact on contemporary cultural production and thinking.
Postmodernism and philosophy / Paul Sheehan -- Postmodernism and film / Catherine Constable -- Postmodernism and literature / Steven Connor -- Postmodernism and art: postmodernism now and again / Stephen Melville -- Postmodernism and performance / Philip Auslander -- Postmodernism and space / Julian Murphet -- Science, technology and postmodernism / Ursula K. Heise -- Postmodernism and post-religion / Philippa Berry -- Postmodernism and ethics against the metaphysics of comprehension / Robert Eaglestone -- Law and justice in postmodernity / Costas Douzinas.
Includes bibliographical references (p. 224-229) and index.
Keywords: Postmodernism